PRESENCIA DE Neospora caninum EN LLAMAS DE UNA EMPRESA GANADERA DE LA SIERRA CENTRAL - Casas V., Gina (2006)
The Neospora caninum is a protozoan that causes abortion, especially in cattle. Thepresent study was carried out to determine the seroprevalence to Neospora caninum inllamas of the central zone of the country. A total of 175 serum samples of breeding femalellamas of the Agrarian Cooperative Pachacútec were analyzed by the immunofluorescentantibody test (IFAT). The results confirmed the presence of Neospora caninum in llamasof the Central Sierra, but the seroprevalence was low (2.9 ± 2.5 %).